2021
DOI: 10.1097/corr.0000000000002055
|View full text |Cite
|
Sign up to set email alerts
|

Prior Intra-articular Corticosteroid Injection Within 3 Months May Increase the Risk of Deep Infection in Subsequent Joint Arthroplasty: A Meta-analysis

Abstract: Background Intra-articular injections containing a corticosteroid are used frequently, and periprosthetic joint infection is a serious complication after total joint arthroplasty. There is debate regarding whether intraarticular corticosteroid injections before arthroplasty increase periprosthetic joint infection after surgery. Questions/purposes (1) Does a previous intra-articular corticosteroid injection increase the odds of infection after subsequent hip or knee arthroplasty? (2) Does this risk vary based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 45 publications
1
37
0
Order By: Relevance
“…Despite that, the two metaanalyses concluded that there was an increased risk of infection in patients who had received prior IAIs. 38,39 One potential factor leading to the variance and difference in these conclusions is the larger patient population size in some of the more recent publications. It is also notable that these two metaanalyses combined data from THA and TKA studies to interpret the effect of preoperative IAIs on joint arthroplasty as a whole, not specific to the hip or knee.…”
Section: Newer Evidencementioning
confidence: 99%
“…Despite that, the two metaanalyses concluded that there was an increased risk of infection in patients who had received prior IAIs. 38,39 One potential factor leading to the variance and difference in these conclusions is the larger patient population size in some of the more recent publications. It is also notable that these two metaanalyses combined data from THA and TKA studies to interpret the effect of preoperative IAIs on joint arthroplasty as a whole, not specific to the hip or knee.…”
Section: Newer Evidencementioning
confidence: 99%
“…I'm concerned that the answer to one or both of those questions may be "yes." In the current study [4], the first question was explored, but the spread of the 95% CI made me wonder whether more data will change the authors' no-difference conclusion. The second of those questions remains, as far as I know, unanswered.…”
mentioning
confidence: 97%
“…The opinions expressed are those of the writers, and do not reflect the opinion or policy of CORR ® or The Association of Bone and Joint Surgeons ® . in a robust way, we believe it should have been included in the meta-analysis of Lai et al [5]. Chitre et al [1] included 36 patients as an injection group, and although the small sample size is insufficient to state that ipsilateral steroid injection does not increase the risk of postoperative complications in THA, we believe that it should still be included in this meta-analysis.…”
mentioning
confidence: 99%
“…If the inclusion criteria for this article included studies of corticosteroid intra-articular injection in combination with other medication types, the authors missed four trials eligible for inclusion in their review. One retrospective study of 40 patients who received an intra-articular steroid injection prior to TKA found no infections [9]; of course, a study of this size is too small to make claims of safety with respect to an endpoint as uncommon as infection, and those authors probably should not have done so, we believe this study should have been included in the meta-analysis in CORR ® [5]. Their injection regimen was a mixture of depo methylprednisolone and bupivacaine.…”
mentioning
confidence: 99%